New understanding of gut microbiota and colorectal anastomosis leak: A collaborative review of the current concepts - Liu, Yang; Li, Bowen; Wei, Yunwei (Frontiers in Cellular and Infection Microbiology, 2022)
Anastomotic leak (AL) is a life-threatening postoperative complication following colorectal surgery, which has not decreased over time. Until now, no specific risk factors or surgical technique could be targeted to improve anastomosis healing. In the past decade, gut microbiota dysbiosis has been recognized to contribute to AL, but the exact effects are still vague. In this context, interpretation of the mechanisms underlying gut microbiota contribute to AL is significant for improving patients' outcomes. This review concentrates on novel findings to explain how AL patients' gut microbiota altered, how the AL-specific pathogen colonizes and is enriched on anastomosis site, and how these pathogens conduct their tissue breakdown effects. We build up a framework between the gut microbiota and AL on three levels. Firstly, factors that shape the gut microbiota profiles in patients who developed AL after colorectal surgery include preoperative intervention and surgical factors. Secondly, AL-specific pathogenic or collagenase bacteria adhere to the intestinal mucosa and defend against host clearance, including the interaction between bacteria adhesion and host ECM, the biofilm formation, and weakened host commercial bacterial resistance. Thirdly, we interpret the potential mechanisms of pathogens induced poor anastomotic healing.